2012
DOI: 10.1093/carcin/bgs156
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-emodin suppresses prostate cancer by targeting the mTOR complex 2

Abstract: Phosphatidylinositol 3-kinase (PI3-K) amplification and phosphatase and tensin homolog (PTEN) deletion-caused Akt activation contribute to the development of prostate cancer. Mammalian target of rapamycin complex 2 (mTORC2) is a kinase complex comprised of mTOR, Rictor, mSin1, mLST8/GβL and PRR5 and functions in the phosphorylation of Akt at Ser473. Herein, we report that mTORC2 plays an important role in PC3 androgen refractory prostate cell proliferation and anchorage-independent growth. Aloe-emodin, a natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 31 publications
(40 reference statements)
6
37
0
2
Order By: Relevance
“…Aloe-emodin induced apoptosis, autophagy and differentiation of glioma cells by inhibiting the action of ERK (54). In the current study, aloe-emodin at low doses inhibited AKT and ERK phosphorylation, which is consistent with a previous study by the present authors on prostate cancer cells (PC3) (36). However, PTEN loss caused strong activation of AKT, which, in turn, attenuated the phospho-ERK signal.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Aloe-emodin induced apoptosis, autophagy and differentiation of glioma cells by inhibiting the action of ERK (54). In the current study, aloe-emodin at low doses inhibited AKT and ERK phosphorylation, which is consistent with a previous study by the present authors on prostate cancer cells (PC3) (36). However, PTEN loss caused strong activation of AKT, which, in turn, attenuated the phospho-ERK signal.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that aloe-emodin induces cell death through S-phase arrest in human tongue squamous cancer SCC-4 cells (38). A previous study by the present authors also indicated that mTORC2 is a target of aloe-emodin, and aloe-emodin can strongly inhibit the AKT activation caused by PTEN loss (36). Aloe-emodin is a natural compound from aloe or Rheum palmatum (39,40).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is claimed to be effective in a variety of applications, but it is potential effect on cancer has been of particular [24] Laboratory Breast cancer Suppressed the proliferation Suboj P et al [25] Laboratory Colon cancer Induced apoptosis Lee HZ et al [26] Laboratory Lung carcinoma Inhibited cell growth in cell lines Chen HC et al [27] Laboratory Promyelocytic leukemia Inhibited cell growth in cell lines Pecere T et al [28] Laboratory Neuroectodermal tumors Inhibited cell growth in cell lines Pan Q et al [29] Laboratory Colorektal cancer Inhibited the angiogenesis through VEGF suppression Yonehara A et al [30] Laboratory Neuroblastoma Suppressing the cyclin D2 transcription level Liu K et al [31] Laboratory Prostate cancer Inhibit cancer cell proliferation by acting through mammalian target of rapamycin complex 2 Heggie S et al [13] Clinical Breast cancer No significant benefit in skin problems caused by radiotherapy Williams MS et al [14] Clinical -No significant benefit in skin problems caused by radiotherapy George J et al [16] Clinical Head and neck cancer Delay the start time of radiotherapy induced skin lesions and reduce their intensity Lissoni P et al [20] Clinical Metastatic cancers Tumor regression Su CK et al [36] Clinical Head and neck cancer No contribution in terms of reducing the symptoms and increasing quality of life interest in recent years. The most advocated benefit of Aloe vera for a cancer patient is its alleged ability to prevent and treat skin lesions caused by radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…[30] In a study on prostate cancer cell cultures (PC3), Aloe emodin was found to inhibit prostate cancer cell proliferation by acting through mammalian target of rapamycin complex 2 (mTORC2) ( Table 1). [31] …”
Section: Laboratory Studies On the Effects Of Aloe Vera On Cancermentioning
confidence: 99%